33 Diagnostic Test Accuracy of the 4AT for Delirium Detection: Systematic Review and Meta-Analysis. (16th March 2021) - Tieges, Z; MacLullich, A M J; Anand, A; Cassaroni, M; O'Connor, M; Ryan, D; Saller, T; Arora, R; Chang, Y; Agarwal, K; Taffet, G; Quinn, T; et al.
Abstract: Introduction: Detection of delirium in hospitalised older adults is recommended in national and international guidelines. The 4 'A's Test (4AT; www.the4AT.com ) is a short (<2 min) instrument for delirium detection that is used internationally as a standard tool in clinical practice. We performed a systematic review and meta-analysis of diagnostic test accuracy of the 4AT for delirium detection. Methods: We searched the following electronic databases through Ovid: MEDLINE, Embase, and PsycINFO. Additional databases were searched: CINAHL (EBSCOhost), clinicaltrials.gov and Cochrane Central Register of Controlled Trials from 2011 (4AT publication) until 21 December 2019. Inclusion criteria: older adults (≥65) across any setting of care except critical care; validation study of the 4AT against a delirium reference standard (standard diagnostic criteria or validated tool). Two reviewers independently screened abstracts and papers and performed the data extraction. Pooled estimates of sensitivity and specificity were generated from a bivariate random effects model. Results: 17 studies (n = 3, 701 observations) were included. Various settings including acute medicine, surgery, stroke wards and the emergency department were represented. The overall prevalence of delirium was 24.2% (95% CI 17.8–32.1%; range 10.5–61.9%). The pooled sensitivity was 0.88 (95% CI 0.80–0.93) and the pooled specificity was 0.88 (95% CI 0.82–0.92). The methodological quality of studies was mostly good. Conclusions: The 4AT is now supported by a substantial evidence base comparable to other well-studied tools such as the Confusion Assessment Method (CAM). The strong pooled sensitivity and specificity findings for the 4AT in this meta-analysis along with its brevity and lack of need for specific training provide support for its use as an effective assessment tool for delirium.